Beginning SUSE Linux 2nd Edition - Thomas, Keir (Apress, 2012)
Linux has come a long way in a short time. Computing itself is still relatively young by any standard; if the era of modern computing started with the invention of the microchip, it’s still less than 50 years old. But Linux is a youngster compared even to this; it has been around for only 15 of those years. In that brief time span, a student’s personal project has grown to where it now runs many computers throughout the world. It has rampaged through the computing industry, offering an alternative to commercial solutions such as those offered by Microsoft, and toppling longheld beliefs about the way things should be done. This is all by virtue of the fact that Linux is simply better than every other choice out there. Many argue that it’s more secure and faster than other operating systems. But here’s the kicker—Linux is free of charge. Yes, that’s right. It doesn’t have to cost a penny. It is one of the computing industry’s best-kept secrets. I was bitten by the Linux bug in the mid-1990s. I was introduced to it by a friend who sold it to me as a kind of alternative to DOS. At that time, I tapped a few commands at the prompt and was greeted by error messages. I must admit that I was put off. But shortly afterward, I revisited Linux and quickly became hooked. Yet getting used to Linux wasn’t easy. I read as many books as I could, but they weren’t very helpful to me. They were usually overly complicated or simply irrelevant. To start off, I didn’t want to know how to create a program that could parse text files. I just wanted to know how to copy and delete files. I didn’t want to set up a web server. I just wanted to know how to play my MP3 tracks and browse the Web